Monocrystalline semiconductor CdS nanosheet and preparation method and application thereof

The preparation of single-crystal CdS nanosheets by vapor deposition solves the problem of poor photocatalytic performance of single-crystal CdS materials in the prior art, and achieves efficient photocatalytic water splitting to produce hydrogen, with high crystallinity and good stability.

CN116288726BActive Publication Date: 2026-11-06SOUTH CHINA AGRICULTURAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310281092.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-20
Publication Date
2026-11-06
Estimated Expiration
2043-03-20

AI Technical Summary

Technical Problem

Existing technologies struggle to synthesize efficient single-crystal CdS two-dimensional materials for photocatalytic water splitting to produce hydrogen, and existing methods mostly employ one-dimensional nanowire structures, resulting in poor photocatalytic performance and insufficient stability.

Method used

By controlling the temperature and molar ratio under an inert atmosphere using vapor deposition, Cd source and S powder react to generate single-crystal semiconductor CdS nanosheets, which are then deposited on the surface of a glass slide to prepare highly crystalline single-crystal CdS nanosheets.

Benefits of technology

The prepared single-crystal CdS nanosheets exhibit excellent visible light absorption performance and high photocatalytic efficiency, resulting in a high rate of hydrogen production through photocatalytic water splitting. Furthermore, they do not require compositing with other semiconductors and demonstrate good stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116288726B_ABST
    Figure CN116288726B_ABST
Patent Text Reader

Abstract

This invention discloses a single-crystal CdS nanosheet, its preparation method, and its applications, relating to the field of photocatalytic nanomaterials technology. The invention prepares single-crystal CdS nanosheets via vapor deposition. These nanosheets possess a narrow band gap and an absorption band edge of 590 nm, exhibiting strong visible light absorption and excellent photocatalytic performance. Furthermore, since they do not require compositing with other semiconductors to enhance stability, they maximize the photocatalytic performance of CdS, making them particularly suitable for photocatalytic water splitting to produce hydrogen.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photocatalytic nanomaterials technology, and more specifically, to a single-crystal semiconductor CdS nanosheet, its preparation method, and its application. Background Technology

[0002] To address the energy crisis and environmental pollution, hydrogen has garnered widespread attention as an ideal alternative to fossil fuels. Methods for hydrogen production include photocatalytic water splitting, electrolyte water methods, and hydrocarbon cracking, with photocatalytic water splitting being the most common. For photocatalysis, selecting a suitable photocatalyst is crucial for enhancing photocatalytic activity. Photocatalytic semiconductors, due to their ability to not only produce hydrogen but also reduce carbon dioxide to hydrocarbons and degrade organic pollutants, are receiving increasing attention.

[0003] Cadmium sulfide (CdS) is a typical photocatalytic semiconductor with a narrow band gap and strong visible light absorption. It exhibits excellent photochemical properties and quantum efficiency in the visible light region, demonstrating good absorption performance not only for visible light wavelengths less than 516 nm but also producing photogenerated carriers with long lifetimes. It is one of the most prominent semiconductor photocatalysts among various sulfides used for hydrogen production, especially two-dimensional CdS materials, which exhibit even better photocatalytic hydrogen production performance. However, CdS belongs to the hexagonal crystal system, with atoms connected by strong chemical bonds in all three dimensions. These intrinsically isotropic bonds result in significant differences in activity between different crystal planes, leading to a tendency to form one-dimensional and three-dimensional morphologies. Furthermore, due to the poor photocatalytic stability of CdS itself, it generally needs to be combined with semiconductors such as TiO2 and g-C3N4, and is not a single-crystal CdS material, thus failing to achieve the ideal photocatalytic hydrogen production performance of CdS. Currently, most commonly used CdS semiconductors synthesized by solvothermal methods are one-dimensional materials, and their photocatalytic water splitting hydrogen production performance is inferior to that of two-dimensional materials. Currently reported synthesis methods for single-crystal CdS are mainly solvothermal (Applied Catalysis B: Environmental).

[0004] 244,5,2019,694-703, J. Mater. Chem. A,2013,1,10927-10934, ACS Appl. Mater. Interfaces 2019,11,41,37586–37594, Journal of Materials Science 2020,55,11167–11176), and vapor deposition (Chem. Mater. 2002,14,4,1773–1777, J. Phys. Chem. B 2005,109,19,9294–9298). These methods all yield one-dimensional nanowire structures, and the vapor deposition method requires prior preparation of CdS, which is disadvantageous for large-scale synthesis.

[0005] Existing technology discloses a vapor-phase preparation method for cadmium group two-dimensional semiconductors (Zhao Mei. Vapor-phase preparation and photoelectric properties of antimony group and cadmium group two-dimensional semiconductors [D]. University of Electronic Science and Technology of China, 2021.). Two-dimensional CdS nanosheets were synthesized by template-assisted vapor-phase preparation method. However, this method is actually a gas-solid reaction, and the synthesized CdS nanosheets are not single crystal materials. The effect in photocatalytic water splitting to produce hydrogen needs to be improved. Summary of the Invention

[0006] In order to overcome the deficiencies and shortcomings of existing single-crystal CdS two-dimensional materials for photocatalytic hydrogen production, this invention provides a single-crystal semiconductor CdS nanosheet, which solves the problem of the lack of existing single-crystal CdS materials. The single-crystal semiconductor CdS nanosheet has a narrow bandgap and wide absorption bandwidth, excellent visible light absorption performance, and high photocatalytic efficiency.

[0007] Another object of the present invention is to provide a single-crystal semiconductor photocatalyst.

[0008] Another object of the present invention is to provide the application of the above-mentioned single-crystal semiconductor photocatalyst in the field of photocatalysis.

[0009] The above-mentioned objective of this invention is achieved through the following technical solution:

[0010] A single-crystal CdS nanosheet, the preparation method of the single-crystal CdS nanosheet includes the following steps:

[0011] The Cd source is heated to 950–1250 °C, while the S powder is heated to 100–150 °C. The reaction is carried out in an inert atmosphere, and the single-crystal semiconductor CdS nanosheets are obtained by cooling and deposition.

[0012] It should be noted that:

[0013] Vapor deposition is a method for synthesizing coatings or nanomaterials by reacting chemical gases or vapors on the surface of a substrate.

[0014] This invention prepares single-crystal CdS nanosheets via vapor deposition, where the substrate can be a glass sheet. The invention involves controlling the temperature to sublimate Cd source and S powder, mixing them under a flowing inert gas (such as nitrogen), reacting to generate CdS, and then depositing it onto the substrate surface after cooling to obtain single-crystal CdS nanosheets.

[0015] The specific reaction temperature of the Cd source can be 950℃, 1000℃, 1050℃, 1100℃, 1150℃, 1200℃, or 1250℃.

[0016] The reaction temperature of the S powder can specifically be 100℃, 105℃, or 150℃.

[0017] Preferably, the Cd source is heated to 940–960°C, more preferably to 950°C.

[0018] Preferably, the S powder is heated to 100-105°C, more preferably to 100°C.

[0019] Specifically, the molar ratio of Cd to S is 1:(1~10), for example, it can be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, or 1:10.

[0020] More specifically, the molar ratio of Cd to S is 1:(1-3), preferably 1:1.

[0021] The molar ratio of Cd to S affects the yield of single-crystal semiconductor CdS nanosheets.

[0022] Specifically, the reaction time is 0.5 to 12 hours, for example, it can be 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours, 8.5 hours, 9 hours, 9.5 hours, 10 hours, 10.5 hours, 11 hours, 11.5 hours, or 12 hours; more specifically, it is 2 hours.

[0023] By controlling the reaction time, the Cd source and S powder can be better ensured to react fully, and single-crystal semiconductor CdS nanosheets were successfully obtained.

[0024] Specifically, the Cd source is CdCl2 or Cd(NO)3.

[0025] Specifically, the absorption band edge of the single-crystal semiconductor CdS nanosheet is 590 nm, and the corresponding band width (i.e., band gap) is 2.07 V.

[0026] Specifically, the flat band potential of the single-crystal semiconductor CdS nanosheet is -0.70 eV, and the corresponding conduction band potential and valence band potential are -0.90 eV and 1.17 eV, respectively.

[0027] The flat band potential of CdS affects the conduction band potential, and the conduction and valence band potentials affect the redox properties of the material, thereby affecting its catalytic performance.

[0028] To date, there have been no reports on the synthesis of single-crystal CdS nanosheets via vapor deposition. This invention successfully prepared single-crystal CdS nanosheets via vapor deposition, broadening the research scope of photocatalysts. Furthermore, the obtained single-crystal CdS nanosheets exhibit excellent performance as a photocatalyst for photocatalytic water splitting to produce hydrogen. In addition, the single-crystal CdS nanosheets prepared in this invention possess suitable valence band and conduction band positions, meeting the thermodynamic requirements for photocatalytic water splitting to produce hydrogen.

[0029] The method for preparing single-crystal semiconductor CdS nanosheets described in this invention is simple to operate, widely applicable, and highly reproducible, providing a reliable solution for reducing photocatalysis costs and for photocatalytic hydrogen production.

[0030] This invention specifically protects a single-crystal semiconductor photocatalyst, wherein the single-crystal semiconductor photocatalyst includes the aforementioned single-crystal semiconductor CdS nanosheets.

[0031] The single-crystal CdS nanosheets obtained in this invention exhibit high surface crystallinity, few defects, and consistent orientation, which is beneficial for the separation of photogenerated carriers. Furthermore, their single-crystal structure results in a narrow semiconductor band gap and a wide light absorption range, leading to high light utilization. When applied to photocatalysts, these nanosheets demonstrate excellent photocatalytic activity and high catalytic efficiency. Moreover, the single-crystal CdS nanosheets described in this invention exhibit good photocatalytic stability without requiring combination with other semiconductors.

[0032] This invention particularly protects the application of the above-mentioned single-crystal semiconductor photocatalyst in the field of photocatalysis.

[0033] Specifically, the single-crystal semiconductor photocatalyst is used for photocatalytic water splitting to produce hydrogen.

[0034] The aforementioned single-crystal semiconductor photocatalyst comprises the single-crystal CdS nanosheets of this invention. As an n-type semiconductor, the CdS nanosheets have a narrow band gap. Under visible light irradiation, the CdS nanosheets are excited to generate photo-generated electrons and holes. The photo-generated electrons transition from the valence band to the conduction band of the CdS nanosheets, while the holes remain in their valence band. The photo-generated electrons combine with water in the conduction band of the CdS nanosheets to undergo a reduction reaction, producing hydrogen gas. Simultaneously, the holes remaining in the valence band react with sodium sulfite, completing the photocatalytic decomposition of water to produce hydrogen.

[0035] Therefore, the single-crystal semiconductor CdS nanosheets of the present invention can be effectively applied in photocatalytic reaction systems, especially in photocatalytic water splitting to produce hydrogen, where they can play a highly efficient catalytic role.

[0036] Specifically, the photocatalytic water-to-hydrogen production includes the following steps:

[0037] The single-crystal semiconductor CdS nanosheets were mixed with a sacrificial agent and water, placed under anaerobic conditions, and illuminated to produce hydrogen gas.

[0038] Specifically, the ratio of the mass of the single-crystal semiconductor CdS nanosheet to the total volume of the sacrificial agent and water can be conventionally selected according to actual needs.

[0039] In a specific embodiment, the mass ratio of the single-crystal semiconductor CdS nanosheet to the total volume of the sacrificial agent and water is 50 mg: 80 mL.

[0040] Specifically, the anaerobic condition is an inert atmosphere.

[0041] Specifically, the sacrificial agent accounts for 5% to 30% of the total volume of water and sacrificial agent.

[0042] Specifically, the sacrificial agent is sodium sulfate, sodium sulfite, or a mixed solution of sodium sulfate and sodium sulfite.

[0043] Specifically, the light intensity is 160 mV*cm. -2 .

[0044] Specifically, the wavelength λ of the light source is greater than 420 nm.

[0045] The above wavelengths are usually obtained by installing a UV filter on the light source.

[0046] Specifically, the light sources providing illumination include, but are not limited to, xenon lamps, Xe arc lamps, and high-pressure mercury lamps, with a power of 300–350W.

[0047] Compared with the prior art, the beneficial effects of the present invention are:

[0048] This invention prepares single-crystal CdS nanosheets by vapor deposition. The single-crystal CdS nanosheets have a narrow band gap and an absorption band edge of 590 nm, exhibiting strong visible light absorption and excellent photocatalytic effect. Furthermore, since they do not require compositing with other semiconductors to improve stability, they can maximize the photocatalytic performance of CdS, making them particularly suitable for the field of photocatalysis.

[0049] The single-crystal CdS nanosheets described in this invention achieve a hydrogen production rate of 52.4 mmol·h⁻¹ in the photocatalytic water splitting hydrogen production reaction. -1 ·g -1 Furthermore, it exhibits good photocatalytic cycle stability. Attached Figure Description

[0050] Figure 1 This is a scanning electron microscope (SEM) image of the single-crystal semiconductor CdS nanosheets from Example 1.

[0051] Figure 2 This is a high-resolution transmission electron microscope (HRTEM) image of the single-crystal semiconductor CdS nanosheets from Example 1.

[0052] Figure 3 The image shows the lattice diffraction pattern of the single-crystal semiconductor CdS nanosheets from Example 1.

[0053] Figure 4 This is an atomic force microscope (AFM) image of the single-crystal semiconductor CdS nanosheets from Example 1.

[0054] Figure 5 The image shows the XRD pattern of the single-crystal semiconductor CdS nanosheets from Example 1.

[0055] Figure 6 The image shows the UV-Vis absorption spectrum of the single-crystal semiconductor CdS nanosheets from Example 1.

[0056] Figure 7 The image shows the Mott-Schottky diagram of the single-crystal semiconductor CdS nanosheets from Example 1.

[0057] Figure 8 The image shows the photocatalytic hydrogen production performance of the single-crystal semiconductor CdS nanosheets in Example 1. Detailed Implementation

[0058] The specific steps for photocatalytic water splitting to produce hydrogen in each embodiment of the present invention are as follows:

[0059] (1) Add the single-crystal semiconductor CdS nanosheets prepared in this invention, a sacrificial agent and water to the photocatalytic reactor; the sacrificial agent is sodium sulfite and the volume concentration of the sacrificial agent is 10%; the mass ratio of the single-crystal semiconductor CdS nanosheets to the total volume of the sacrificial agent and water is 50mg:80mL.

[0060] (2) Ultrasonic dispersion of single-crystal semiconductor CdS nanosheets and nitrogen gas to remove air;

[0061] (3) The reactor was irradiated with a 300W xenon lamp, and ultraviolet light was filtered using a filter to ensure that λ > 420nm in the reaction system; the light intensity was 160mV*cm. -2 ;

[0062] (4) Online analysis was performed using gas chromatography.

[0063] In the following examples, CdCl2 and S powder were purchased from Shanghai Maclean Biochemical Technology Co., Ltd.

[0064] In the following examples, the centrifuge used is a high-speed refrigerated centrifuge (model eppendrofcentrifuge5810R).

[0065] The present invention will be further described below with reference to specific embodiments, but the embodiments do not limit the present invention in any way. Unless otherwise stated, the raw materials and reagents used in the embodiments of the present invention are conventionally purchased raw materials and reagents.

[0066] Example 1

[0067] A method for preparing single-crystal CdS nanosheets includes the following steps:

[0068] CdCl2 and S powder were placed in the high-temperature zone and low-temperature zone of a tube furnace, respectively. A glass plate was placed at the end of the high-temperature zone to collect the formed CdS. The high-temperature zone was heated to 950°C, while the low-temperature zone was heated to 100°C. Nitrogen gas was introduced to allow Cd and S to react in a nitrogen atmosphere for 2 hours. After cooling, single-crystal semiconductor CdS nanosheets were obtained. The molar ratio of Cd to S was 1:1.

[0069] The single-crystal CdS nanosheets prepared above have a single-crystal structure, an absorption band edge of 590 nm, and a corresponding band width of 2.07 eV. The flat band potential of the single-crystal CdS nanosheets is -0.70 eV, and the corresponding conduction band potential and valence band potential are -0.90 eV and 1.17 eV, respectively.

[0070] Example 2

[0071] A method for preparing single-crystal CdS nanosheets includes the following steps:

[0072] CdCl2 and S powder were placed in the high-temperature zone and low-temperature zone of a tube furnace, respectively. A glass plate was placed at the end of the high-temperature zone to collect the formed CdS. The high-temperature zone was heated to 950°C, while the low-temperature zone was heated to 100°C. Nitrogen gas was introduced to allow Cd and S to react in a nitrogen atmosphere for 2 hours. After cooling, single-crystal semiconductor CdS nanosheets were obtained. The molar ratio of Cd to S was 1:2.

[0073] The single-crystal CdS nanosheets prepared above have a single-crystal structure, an absorption band edge of 590 nm, and a corresponding band width of 2.07 eV. The flat band potential of the single-crystal CdS nanosheets is -0.70 eV, and the corresponding conduction band potential and valence band potential are -0.90 eV and 1.17 eV, respectively.

[0074] Example 3

[0075] A method for preparing single-crystal CdS nanosheets includes the following steps:

[0076] CdCl2 and S powder were placed in the high-temperature zone and low-temperature zone of a tube furnace, respectively. A glass plate was placed at the end of the high-temperature zone to collect the formed CdS. The high-temperature zone was heated to 950°C, while the low-temperature zone was heated to 100°C. Nitrogen gas was introduced to allow Cd and S to react in a nitrogen atmosphere for 2 hours. After cooling, single-crystal semiconductor CdS nanosheets were obtained. The molar ratio of Cd to S was 1:3.

[0077] The single-crystal CdS nanosheets prepared above have a single-crystal structure, an absorption band edge of 590 nm, and a corresponding band width of 2.07 eV. The flat band potential of the single-crystal CdS nanosheets is -0.70 eV, and the corresponding conduction band potential and valence band potential are -0.90 eV and 1.17 eV, respectively.

[0078] Comparative Example 1

[0079] A method for preparing polycrystalline CdS includes the following steps:

[0080] 2 mmol of cadmium acetate and 6 mmol of thiourea were added to 60 mL of ethylenediamine solution and stirred for 30 minutes. The mixture was then heated at 100 °C for 8 hours in a polytetrafluoroethylene-lined autoclave. After that, the yellow sample was washed three times with deionized water and ethanol to obtain polycrystalline CdS.

[0081] Result detection

[0082] Photocatalytic reaction activity test:

[0083] The reaction apparatus consisted of a 150 mL quartz reactor, with a 300 W xenon lamp as the light source. A UV filter (λ>420 nm) was installed in front of the lamp head. The light intensity at the location of the quartz reactor was 150 mV*cm. -2 .

[0084] 50 mg of the samples prepared in the above examples and comparative examples were added to a quartz reactor containing a mixed solution of sodium sulfide, sodium sulfite, and deionized water. Before the light exposure test, the suspension was sonicated for 30 min, and then nitrogen gas was introduced into the quartz reactor for 30 min to ensure that the reaction test was carried out under anaerobic conditions. After 1 h of light exposure, 0.4 mL of gas was taken out from the quartz reactor using a 1 mL syringe and analyzed using a GC-9500 gas chromatograph (Ar as carrier gas). The results are shown in Table 1.

[0085] Table 1. Photocatalytic water splitting hydrogen production rate of single-crystal CdS nanosheets

[0086] <![CDATA[Average hydrogen production rate (mmol·h -1 ·g -1 )]]> Example 1 52.4 Example 2 51.2 Example 3 51.9

[0087] As can be seen from Table 1, the average photocatalytic hydrogen production rate of the single-crystal CdS nanosheets described in this invention is 50 mmol·h within 1 h. -1 ·g -1 The highest level reached was 52.4 mmol / h. -1 ·g -1 This demonstrates that the single-crystal semiconductor CdS nanosheets obtained by this invention have excellent photocatalytic effects.

[0088] Figure 1 The image shows a scanning electron microscope (SEM) image of the single-crystal semiconductor CdS nanosheets of Example 1. It can be clearly seen from the image that the single-crystal semiconductor CdS nanosheets obtained by the present invention have a two-dimensional nanosheet structure.

[0089] Figure 2 This is a high-resolution transmission electron microscope (HRTEM) image of single-crystal CdS nanosheets from Example 1. Figure 3 The lattice diffraction pattern of the single-crystal semiconductor CdS is shown below. Figure 2 The regular lattice orientation indicates high crystallinity; from Figure 3 The symmetrical diffraction patterns demonstrate that the single-crystal CdS nanosheets do indeed possess a single-crystal structure. Therefore, the single-crystal CdS nanosheets obtained in this invention exhibit a highly crystalline single-crystal structure.

[0090] Figure 4 This is an atomic force microscope (AFM) image of the single-crystal CdS nanosheets from Example 1, combined with... Figure 1 and Figure 4 As can be seen, the single-crystal semiconductor CdS nanosheets obtained by this invention have a nanosheet structure and a nanometer thickness of 5 nm, making them nanomaterials.

[0091] Figure 5 The image shows the XRD pattern of the single-crystal CdS nanosheets of Example 1. It can be seen from the image that the diffraction peaks of the single-crystal CdS nanosheets of this invention correspond one-to-one with the diffraction peaks on the standard card.

[0092] Figure 6 The image shows the UV-Vis absorption spectrum of the single-crystal CdS nanosheets obtained in Example 1. As can be seen from the image, the absorption band edge of the single-crystal CdS nanosheets obtained in this invention is close to 590 nm, and the corresponding bandwidth is 2.07 eV.

[0093] Figure 7 The image shows the Mott-Schottky diagram of the single-crystal CdS nanosheets of Example 1. It can be seen that the flat band potential of the single-crystal CdS nanosheets of the present invention is -0.70 eV, and the corresponding conduction band potential and valence band potential are -0.9 eV and 1.17 eV, respectively.

[0094] Figure 8 The graph shows the photocatalytic hydrogen production performance of the single-crystal CdS nanosheets in Example 1. As can be seen from the graph, the average photocatalytic hydrogen production rate of the single-crystal CdS nanosheets described in this invention is 52.4 mmol / h. -1 g -1 The hydrogen production rate of polycrystalline CdS is only 4.82 mmol / h. -1 g -1 This demonstrates that the single-crystal semiconductor CdS nanosheets of the present invention have a high photocatalytic water splitting hydrogen production rate.

[0095] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. Use of a single-crystalline semiconductor CdS nanosheet as a single-crystalline semiconductor photocatalyst in photocatalytic hydrogen production from water splitting, characterized in that, The method for preparing the single-crystal semiconductor CdS nanosheets includes the following steps: The Cd source is heated to 950~1250℃, and the S powder is heated to 100~150℃. The reaction is carried out in an inert atmosphere, and the single crystal semiconductor CdS nanosheets are obtained by cooling and deposition. The photocatalytic water-to-hydrogen production method includes the following steps: mixing the single-crystal semiconductor CdS nanosheets with a sacrificial agent and water, placing them under anaerobic conditions, providing light, and reacting to produce hydrogen gas; the sacrificial agent is sodium sulfate, sodium sulfite, or a mixed solution of sodium sulfate and sodium sulfite; the wavelength of the light irradiation is λ>420nm.

2. The use according to claim 1, characterized in that, The Cd source is heated to 950~960℃.

3. The use according to claim 1, characterized in that, The S powder is heated to 100~105℃.

4. The use according to claim 1, characterized in that, The molar ratio of Cd to S is 1:(1~10).

5. The use according to claim 4, wherein the compound is ###0002### The molar ratio of Cd to S is 1:(1~3).

6. The application as described in claim 1, characterized in that, In the preparation method of the single-crystal semiconductor CdS nanosheets, the reaction time is 0.5~12h.

7. The application as described in claim 1, characterized in that, The Cd source is CdCl2.

Citation Information

Patent Citations

  • Preparation method of cadmium selenide or cadmium sulfide two-dimensional monocrystal nanosheet

    CN105463580A

  • Preparation and application of cadmium sulfide nanosheet

    CN109574066A